2020
DOI: 10.1049/bme2.12002
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐ethnicity face anti‐spoofing recognition challenge: A review

Abstract: Face anti‐spoofing is critical to prevent face recognition systems from a security breach. The biometrics community has achieved impressive progress recently due to the excellent performance of deep neural networks and the availability of large datasets. Although ethnic bias has been verified to severely affect the performance of face recognition systems, it still remains an open research problem in face anti‐spoofing. Recently, a multi‐ethnic face anti‐spoofing dataset, CASIA‐SURF cross‐ethnicity face anti‐sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 42 publications
0
30
0
2
Order By: Relevance
“…Finally, we found that our dataset was not balanced in terms of race, which is a key point for face detection, as mentioned in [27,28]. The authors of [28] constructed a balanced race dataset, including White, Black, Indian, East Asian, Southeast Asian, Middle East, and Latino faces.…”
Section: Problems and Limitationsmentioning
confidence: 93%
“…Finally, we found that our dataset was not balanced in terms of race, which is a key point for face detection, as mentioned in [27,28]. The authors of [28] constructed a balanced race dataset, including White, Black, Indian, East Asian, Southeast Asian, Middle East, and Latino faces.…”
Section: Problems and Limitationsmentioning
confidence: 93%
“…Ma et al [49] proposed a multi-regional CNN with the local binary classification loss to local patches. Yu et al [13] utilized pixel-wise binary label to supervise the multimodal CDCN and won the first place in the ChaLearn multi-modal face anti-spoofing attack detection challenge @CVPR2020 [74]. With the help of spatially positional knowledge, binary mask label not only boosts the models' discrimination, but also benefits neural architecture search.…”
Section: Review Of Pixel-wise Supervisionmentioning
confidence: 99%
“…Алиа в [4] и Зун и др. в [5] придумали метод запроса пользователя на выполнение некоторой случайной инструкции, а затем проверенного ответа, чтобы подтвердить, были ли инструкции выполнены или нет.…”
Section: обзорunclassified